GAMBARAN TINGKAT KETERAMPILAN SOSIAL SISWA DALAM MEWUJUDKAN INKLUSI SOSIAL DAN PERAN GURU BK DI SEKOLAH DASAR - Tita Rosita; Raden Mutiara Puspa Wijaya (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The purpose of this study was to determine the level of students' social skills in the implementation of social inclusion and the role of guidance counselors in public elementary schools. The research method used was quantitative with a survey approach. The research sample consisted of 137 fourth and fifth grade students at Public Elementary School 08 Lubang Buaya in Jakarta. The criteria for students who filled out the questionnaire were that they were peers who had friends with disabilities in their class. Based on the results of the study, the majority of students had moderate social skills, namely 96 students (70.1%), 26 students (19%) had high social skills, and 16 students (10.9%) had low social skills. These findings indicate that students' abilities to interact, empathize, and accept differences have begun to develop, but have not yet developed optimally. Therefore, the role of guidance counselors is needed to strengthen social skills through individual and group counseling programs to foster empathy, cooperation, and acceptance of differences. This will enable students with special needs to integrate with their peers into the social ecology of the school.